Assessment and prevention of behavioural and social risk factors associated with oral cancer: protocol for a systematic review of clinical guidelines and systematic reviews to inform Primary Care dental professionals. Issue 1 (December 2015) - Mathur, Sweta; Conway, David; Worlledge-Andrew, Heather; Macpherson, Lorna; Ross, Alastair
Abstract Background Tobacco and alcohol are recognised as the major risk factors for both oral cavity (mouth) and oropharyngeal (throat) cancers, with increasing acceptance of the role of human papillomavirus (HPV) in the aetiology of oropharyngeal cancers. In addition, there is a significant increased risk for oral cancer among lower socioeconomic groups, males and older age groups. There is a growing evidence for the potential role ofprimary care professionals in smoking cessation and reducing alcohol-related harm. However, there are uncertainties about the best approaches/strategies to assess risk factors associated with oral cancer, effective components of preventive interventions for behaviour change and implementation strategies in primary care dental settings. Thus, in order to contribute to the prevention of oral cancer effectively, dental professionals need to assess patients on the major risk factors (tobacco, alcohol and HPV/sexual behaviours) and deliver appropriate prevention, taking into account the patient's sociodemographic context. Aim The study aims to synthesise evidence on the best practice for undertaking an assessment of major behavioural risk factors associated with oral cancer and delivering effective behaviour change preventive interventions (e.g. advice, counselling, patient recall, signposting/referral to preventive services) by dental professionals in primary care dental settings. Method The study involves a systematic review and evidence appraisal. We will search for clinical guidelines and systematic reviews from the following databases:Cochrane Library, Ovid MEDLINE, EMBASE, Web of Science, PsychINFO, PubMed, TRIP andGoogle Scholar . We will also search websites of professional organisations/agencies and bibliographies/reference lists of selected papers. Quality will be assessed with the AGREE II (Appraisal of Guidelines for Research & Evaluation II) instrument for included clinical guidelines and the AMSTAR (A Measurement Tool to Assess Systematic Reviews) and ROBIS instruments for included systematic reviews. The best practice evidence will be assessed via a narrative synthesis of extracted data, considering publication quality. Discussion This systematic review will synthesise evidence on the best practice for oral cancer risk factor assessment and prevention and evaluate the relationship between available clinical guidelines and the review evidence base. This collation of evidence will be useful for making recommendations for future intervention, research and guideline development. Systematic review registration PROSPEROCRD42015025289